TRANSLATING A NOVEL: PROBLEMS AND SOLUTIONS (A HOLISTICALLY CRITIQUE ON NOVEL TRANSLATION) - Hartono, Rudi (Language Circle: Journal of Language and Literature, 2009)
Translating a novel is more difficult than translating academic texts. Novel translators (Genetic factor) usually have problems in translating figurative languages (metaphors, similes, personifications, etc.) and idiomatic expressions because they should reproduce in the target language (TL) the closest natural equivalence of the source language (ST) message, firstly in terms of meaning and secondly in terms of style accepted socio-culturally. Other problems come from the translation document (e.g. an English novel translated into Bahasa Indonesia) and readers of the translated novel. The translation document (Objective Factor) has mistakes in equivalence of words. Some expressions are not translated into the acceptable ones in the target language. The readers of translated novel (Affective Factor) are often confused on what they are reading because some sentences are not understandable. The solution of those problems is to provide the novel translators some practical guidance of translating a novel in order to produce the high quality of translation product. ÃÂ  Key words: translation, novel, metaphors, similes, idiomatic expressions, ST (Source Language), TL (Target Language)